Clinical characteristics and risk factors of Hepatitis E virus infection in Zhejiang Province: a multicenter case–control study - Chen, Yijuan; Gao, Jian; Sun, Wanwan; Zhu, Weiping; Wang, Pingping; Ren, Xiaobin; Wu, Yumeng; Zhang, Jianli; Miao, Ziping (Frontiers in Public Health, 2024)
Hepatitis E (HE), caused by the Hepatitis E virus (HEV), is a significant cause of acute viral hepatitis globally and a major public health concern, particularly in specific high-prevalence areas in China, which have diverse transmission routes and regional differences. Identifying the primary risk factors for HE transmission is essential to develop targeted interventions for vulnerable populations. This study employed a 1:1 matched case-control methodology, using a standardized questionnaire complemented by medical records for data validation. Among the 442 HE cases and 428 healthy controls, the case group had a higher prevalence of fatigue (46.21%) and loss of appetite (43.84%) compared to the control group. Furthermore, liver function indicators were significantly higher in the case group, with an average alanine aminotransferase (ALT) level of 621.94 U/L and aspartate aminotransferase (AST) level of 411.53 U/L. Severe HE patients were predominantly male, with significantly increased ALT and AST levels reaching 1443.81 U/L and 862.31 U/L respectively, along with a higher incidence of fatigue (90%) and loss of appetite (75%).Multifactorial analysis indicated that frequent dining out (OR=2.553, 95%CI:1.686-3.868), poor hygiene conditions (OR=3.889, 95%CI:1.399-10.807), and comorbid chronic illnesses (OR=2.275, 95%CI:1.616-3.202) were risk factors for HE infection; conversely, good hygiene practices were protective factors against HE infection (OR=0.698, 95%CI:0.521-0.934). In conclusion, HE infection in Zhejiang Province is closely associated with dietary habits and environmental hygiene, and individuals with chronic diseases or co-infections are at increased risk. This highlights the need for targeted health education to reduce the incidence of HE among these populations.